Risk of fracture in men with prostate cancer on androgen deprivation therapy: a population-based cohort study in New Zealand. Issue 1 (December 2015) - Wang, Alice; Obertová, Zuzana; Brown, Charis; Karunasinghe, Nishi; Bishop, Karen; Ferguson, Lynnette; Lawrenson, Ross
Abstract Background Androgen deprivation therapy (ADT) administered as a prostate cancer treatment is known to exert multiple side effects including bone deterioration leading to bone fracture. The current analysis is to evaluate the burden of fracture risk in the New Zealand prostate cancer (PCa) population treated with ADT, and to understand the subsequent risk of mortality after a fracture. Methods Using datasets created through linking records from the New Zealand Cancer Registry, National Minimal Dataset, Pharmaceutical Collection and Mortality Collection, we studied 25, 544 men (aged ≥40 years) diagnosed with PCa between 2004 and 2012. ADT was categorised into the following groups: gonadotropin-releasing hormone (GnRH) agonists, anti-androgens, combined androgen blockade (GnRH agonists plus anti-androgens), bilateral orchiectomy, and bilateral orchiectomy plus pharmacologic ADT (anti-androgens and/or GnRH agonists). Results Among patients receiving ADT, 10.8 % had a fracture compared to 3.2 % of those not receiving ADT (p < 0.0001). After controlling for age and ethnicity, the use of ADT was associated with a significantly increased risk of any fracture (OR = 2.83; 95 % CI 2.52–3.17) and of hip fracture requiring hospitalisation (OR = 1.82; 95 % CI 1.44–2.30). Those who received combined androgen blockade (OR = 3.48; 95 % CI 3.07–3.96) and bilateral orchiectomy with pharmacologic ADT (OR = 4.32; 95 % CI 3.34–5.58) had the greatest risk of fracture. The fracture risk following different types of ADT was confounded by pathologic fractures and spinal cord compression (SCC). ADT recipients with fractures had a 1.83-fold (95 % CI 1.68–1.99) higher mortality risk than those without a fracture. However, after the exclusion of pathologic fractures and SCC, there was no increased risk of mortality. Conclusions ADT was significantly associated with an increased risk of any fracture and hip fracture requiring hospitalisation. The excess risk was partly driven by pathologic fractures and SCC which are associated with decreased survival in ADT users. Identification of those at higher risk of fracture and close monitoring of bone health while on ADT is an important factor to consider. This may require monitoring of bone density and bone marker profiles.